O efeito de diferentes formas de redução de fornecimento de conhecimento de resultados (CR) na aquisição de habilidades motoras com demandas distintas - Marcio Mario Vieira (2012)
Knowledge of results (KR) has been recognized as an important factor to motor learning. His investigation has been accomplished through countless forms of supply, which have been studied separately in the process of acquisition of motor skills. The results are not yet conclusive about which of these forms of supply is more effective, with the generalization of results hampered by this variable have been tested in different motor skills. Thus, the present study aims to investigate the effect of different forms of reduction KR supply in motor skills acquisition using the same motor task. Seek to assess the generalization of results the effect was investigated in two tasks with specific demands. Positioning with temporal demand and dart throwing with demand for control of the force. A hundred and forty volunteers were randomly distributed in seven experimental groups (n=10) in each experiment according to different forms of reduction KR supply. Group G100 with 100% of relative frequency, group GFRR with reduced relative frequency, group GFA with KR bandwidth, GMED group with average KR, group GSUM with summary KR, group GAUT with self-control KR and GDEC with faded KR. The experiments were consisted of acquisition phase and tests. The results of both experiments showed that G100 was worst results when compared to other different of reducing supply of KR. Still, motor skills with demands distinct suffer different effects of mode of delivery of KR, because the two experiments did not show similar results. In conclusion, the effect of reducing the supply of KR in the acquisition of motor skills, however the forms of reduction produce different effects depending on the demands of the task.